Aquaporin-4 mediates communication between astrocyte and microglia: Implications of neuroinflammation in experimental Parkinson's disease. (11th March 2016) - Sun, H.; Liang, R.; Yang, B.; Zhou, Y.; Liu, M.; Fang, F.; Ding, J.; Fan, Y.; Hu, G.
Highlights: AQP4 deficiency enhanced gliosis in experimental Parkinson's disease. AQP4 deficiency augmented the production of IL-1β and TNF-α in astrocyte cultures. AQP4 deficiency promoted activation of microglial cells in co-cultured system. Abstract: Aquaporin-4 (AQP4), a water-selective membrane transport protein, is up-regulated in astrocytes in various inflammatory lesions, including Parkinson disease (PD). However, the exact functional roles of AQP4 in neuroinflammation remain unknown. In the present study, we investigated how AQP4 participates in the neuroinflammation of PD using AQP4 knockout (KO) mice and astrocyte–microglial co-cultures. We found that AQP4 KO mice exhibited increased basal and inducible canonical NF-κB activity, and showed significantly enhanced gliosis (astrocytosis and microgliosis) in chronic MPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine)/probenecid PD models, companying with the increase in the production of IL-1β and TNF-α in the midbrain. Similarly, AQP4 deficiency augmented the activation of the NF-κB pathway and the production of IL-1β and TNF-α in midbrain astrocyte cultures treated with MPP + (1-methyl-4-phenylpyridinium). Furthermore, AQP4 deficiency promoted activation of microglial cells in the co-cultured system. Our data provide the first evidence that AQP4 modulates astrocyte-to-microglia communication in neuroinflammation, although its effect on astrocyte inflammatory activation remains to be explored.